Implementation of Smart Village in the Development of Bumdes in Doulu Village Based on Website - Winda Erika; Ruly Dwi Arista; Mohammad Yusuf; Mas Eric Wisnu Pradana; Dwi Heri Purwanto (Yayasan Sinergi Multidimensi Kreatif, 2024)
Smart Village is a smart village concept that is innovative in using information technology so that it can improve the quality of the village economy. In the process of implementing smart villages, it is often used in the needs of Bumdes development so that it can be useful for village development. Bumdes is a village-owned business entity that is a legal entity and managed by the village government. Bumdes is created to manage the results of resources in the village for village development. In carrying out its management, a system is needed that can help the village so that the management of Bumdes is transparent. So a website system is needed that can help the village in managing the results of village resources to become a smart village.